Analysis of the Turning Process of 6X8T Gear (Sprocket) at CV. Anugrah Prima Metalindo - Ibnu Khafiz Nasution; Vidi Agung Fragastia (LPPM Universitas Potensi Utama, 2025)
This study analyzes the turning process of a 6X8T gear sprocket at CV. Anugrah Prima Metalindo. The advancement of the manufacturing industry demands efficient and high-quality production processes, particularly in the manufacturing of mechanical components such as sprockets. This research aims to understand the stages of the turning process, identify existing problems, and evaluate the effectiveness of machining parameters in producing high-quality products. The research methodology includes direct observation, qualitative data collection, and technical analysis of the turning process. The tested parameters include spindle speed, tool angle, and casting techniques for the workpiece. The results indicate that variations in tool angles (60°, 70°, and 80°) and spindle speeds (ranging from 200 rpm to 1100 rpm) influence the surface roughness of the workpiece. A spindle speed of 1100 rpm with an 80° tool angle produced the best surface quality. Additionally, several challenges in the casting process were identified, such as air cavity defects and mold misalignment, which affected the final product quality. An evaluation of occupational health and safety (OHS) aspects was also conducted to enhance worker protection during manufacturing operations. The study concludes that optimizing machining parameters can improve the quality of the sprocket turning process, and stricter OHS standards are necessary to enhance workplace safety. Recommendations for improvement include optimizing the sand mold mixture, refining mold design, and ensuring the use of personal protective equipment for workers.